Tekno tulong - Science and Technology Information Institute. Information Resources and Analysis Division (Taguig IRAD-STII DOST, 2005)
Contains information on various technologies for the Filipino entrepreneur, including manufacture of popular products such as candles, perfume, ice cream, and coconut delicacies.
book 1. Food processing (97 p.) -- book 2. Small industries (731 p.) -- book 3. Herbal medicines (70 p.) -- book 4. Farming (41 p.) -- book 5. Animal husbandry / compiled by Leonor R. Arcilla (45 p.) -- book 6. Fish processing (17 p.) -- book 7. Virgin coconut oil (22 p.) -- book 8. Libraries for all! : how to start and run a basic library / by Laura Wendell (51 p.) -- book 9. How to establish a multi-purpose community telecenter in Africa / by Mike Jensen and Andriette Esterhuysen (136 p.) -- book 10. Home composting (10 p.) -- book 11. Guide to resources for NGOs and other organizations of civil society / Small Grants Program, Social Development Department, World Bank (70 p.)
Summary from foreword.
System requirements: Adobe Acrobat Reader.
Keywords: New business enterprises -- Management; Entrepreneurship; Small business; Food industry and trade; Herbs -- Therapeutic use; Farm management; Fishing; Library planning -- Handbooks, manuals, etc; Telecommunication -- Africa; Refuse and refuse disposal -- Biodegradation; Grants-in-aid.; Development assistance; Electronic books